2010
DOI: 10.1007/s13213-010-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular identification of wine yeasts from a Brazilian vineyard

Abstract: Traditional winemaking is carried out by spontaneous yeasts from the vineyard that persist throughout the alcoholic fermentation. This study examined the diversity of yeast species isolated from grape skin and musts of two varieties of Vitis labrusca from a vineyard in the southeast region of Brazil (Jales, São Paulo), which produces artisanal wines. Molecular identification was achieved by a combination of PCR-RFLP/sequencing of the internal transcribed spacers (ITS) and sequencing of the D1/D2 domain of ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 18 publications
4
24
2
Order By: Relevance
“…terricola and S . bacillaris are also commonly reported as associated with grapes and wine environments [23,46,6265]. However, in this study, both species occurred in higher proportions in comparison to other wine-producing areas.…”
Section: Discussioncontrasting
confidence: 54%
“…terricola and S . bacillaris are also commonly reported as associated with grapes and wine environments [23,46,6265]. However, in this study, both species occurred in higher proportions in comparison to other wine-producing areas.…”
Section: Discussioncontrasting
confidence: 54%
“…terricola is well known for its occurrence in grapes of several varieties throughout the word (Baffi et al 2011), however in this study, it was detected only in the organic Murisengo vineyard. The connection between this species and the organic conduction of the vineyard has not being demonstrated.…”
Section: Pullulanscontrasting
confidence: 55%
“…Restriction analysis has demonstrated that yeast species can be differentiated by combining the action of different restriction endonucleases (Baffi et al 2011, Cordero-Bueso et al 2011, Esteve-Zarzoso et al 1999. The results obtained through this approach are usually complemented with other techniques, in order to confirm the species identification especially when the 5.8-ITS pattern has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…In Vitis vinifera L. grapes, the more relevant non- Saccharomyces species include the apiculate yeasts Hanseniaspora and a large proportion of yeasts from the Metschnikowia and Candida genera (Garofalo et al, 2015; Albergaria and Arneborg, 2016). H. uvarum , present at later stages during fermentation of Vitis vinifera L. grape must (Zott et al, 2008; Padilla et al, 2016a), was also found in spontaneously fermenting Isabella (Baffi et al, 2010; Bezerra-Bussoli et al, 2013; Hong and Park, 2013). Isabella H. uvarum , however, markedly decreased at the mid-stages of fermentation.…”
Section: Discussionmentioning
confidence: 94%